The Lord of the rings the return of the king - Jackson, Peter; Osborne, Barrie M.; Walsh, Fran (Los Angeles, Calif. : New Line Home Entertainment, 2004)
Frodo makes his way through the darkness to Mount Doom to destroy the One Ring. Aragon learns of his destiny as the true King and the others prepare for a massive battle that will determine the fate of Middle-Earth
Disc 2 contains several added features: The quest fulfilled, a director's vision ; A filmmaker's journey: making'The Return of the King;' National Geographic special:'The Lord of the Rings: The Return of the King;' featurettes, original theatrical trailers and TV spots, trilogy supertrailer, a look at Electronic Arts'video games and DVD-Rom content
Title from container
Based on the book by J.R.R. Tolkien
Subtitles in English and Spanish
Screenplay by Fran Walsh & Philippa Boyens & Peter Jackson ; executive producer, Mark Ordesly ; director of photography, Andrew Lesnie ; editor, Jamie Selkirk ; music, Howard Shore ; costume designers, Ngila Dickson, Richard Taylor ; production designer, Grant Major ; visual effects supervisor, Jim Rygiel
Casts: Elijah Wood, Ian Mckellen, Liv Tyler, Viggo Mortensen, Sean Astin, Cate Blanchett, John Rhys-Davies
Keywords: Horror films; Middle Earth (Imaginary place) -- Drama; Fantasy fiction, English -- Film and video adaptations; Adventures films; Baggins, Frodo (Fictitious character) -- Drama